Physico-Chemical Properties of Gembili (Dioscorea esculenta L.) Flour from White-fleshed and Purplish-White-fleshed Tubers - Pamungkas, Wiyan Afriyanto; jamaludin, jamaludin (Jurnal Keteknikan Pertanian, 2024)
Flour quality in the form of physicochemical and sensory properties is an essential parameter that will influence the design, process, and results of the processing of gembili flour derivative products. This study aims to evaluate flour’s physical and chemical properties from white-fleshed gembili tubers (Yawal Porei) and purplish-white-fleshed gembili tubers (Thai) and determine consumer preferences for the flour produced. The physical properties of gembili flour were analyzed, including yield, whiteness, and fineness modulus (FM). Meanwhile, the chemical composition of the flour analyzed includes moisture content, carbohydrates, protein, ash content and crude fibre. 35 untrained panellists were used in organoleptic tests to assess consumer preferences. The results show that the two gembili tubers produce flour with different physical and chemical properties. White-fleshed gembili flour has several advantages in terms of physical and chemical properties, namely yield (15.62% ± 0.41), whiteness (79.55 ± 0.98), carbohydrates (82.86% ± 0.21) and crude fibre (5.28% ± 0.61) which has the potential as a rice analogue, noodles, cake, fillers, and cookies. Meanwhile, purplish-white-fleshed gembili flour has a high protein content (5.40% ± 0.16) and ash content (6.75% ± 0.05), which has the potential as a bakery product. The FM of the two types of gembili flour was not much different and has a moisture content that meets the Indonesian National Standard, below 14.5%. The sensory assessment showed that the panellists preferred white-fleshed gembili flour to purplish-white-fleshed gembili flour. The sensory assessment showed that the panellists preferred white-fleshed gembili flour to purplish-white-fleshed gembili flour.